2019
DOI: 10.1055/a-0874-6603
|View full text |Cite
|
Sign up to set email alerts
|

Colitis ulcerosa: Kann eine Modulation der intestinalen Mikrobiota eine langfristige Remission bedingen?

Abstract: ZusammenfassungDas Verständnis der Colitis ulcerosa (CU) ist in den letzten Dekaden stetig gewachsen; unterschiedliche Therapiekonzepte sind für verschiedene Krankheitssituationen standardisiert. In der Pathogenese wird der gastrointestinalen Mikrobiota, Umweltfaktoren, überschießenden immunologischen Reaktionen und genetischen Faktoren eine immer größere Bedeutung zugeordnet. So zeigen zahlreiche klinische Beobachtungen eine enge Verbindung zwischen einer dysbiotischen Mikrobiota und der Erstmanifestation und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Multiple case studies and several randomized trials have explored this concept in patients with IBD. While most randomized studies involving patients with UC revealed that FMT had a significant impact on induction of remission (Stallmach et al, 2019;Tan et al, 2020), its efficacy has not been verified for patients with CD. Placebo-controlled trials involving patients with UC revealed that, although one out of every 3 to 4 patients achieved remission after FMT, one-time or short-term FMT leads to clinical failure over time.…”
Section: Fecal Microbiota Transplantation: Ready For Prime Time?mentioning
confidence: 99%
“…Multiple case studies and several randomized trials have explored this concept in patients with IBD. While most randomized studies involving patients with UC revealed that FMT had a significant impact on induction of remission (Stallmach et al, 2019;Tan et al, 2020), its efficacy has not been verified for patients with CD. Placebo-controlled trials involving patients with UC revealed that, although one out of every 3 to 4 patients achieved remission after FMT, one-time or short-term FMT leads to clinical failure over time.…”
Section: Fecal Microbiota Transplantation: Ready For Prime Time?mentioning
confidence: 99%
“…The discovery and characterization of a vast number of animal models of intestinal inflammation have greatly advanced our understanding of the pathogenesis of IBD [ 65 ]. These models have provided extensive data to support the general hypothesis that IBD results from a dysregulated immune response, triggered by environmental factors in a genetically susceptible host [ 66 ]. Innate mice provide a unique opportunity to study the influence of predisposing genes and environmental factors in the pathogenesis of IBD.…”
Section: Spontaneous Mutation Mouse Modelsmentioning
confidence: 99%
“…In this regard, the increases of inflammatory cytokines and oxidative stress are known as important incentives to the occurrence and development of UC [5]. Furthermore, extensive studies elucidated the key role of the gut microbiota in the pathogenesis of UC, which postulated that intestinal flora disorders and the occurrence of enteritis also have a close relationship [6][7][8]. Compositional and metabolic imbalance in the intestinal microbiota could change the intestinal mucosal permeability, concomitantly with the infiltrations of pathogenic bacteria and toxins, leading to long-term inflammatory stimulation and even canceration of the colon mucosa [9,10].…”
Section: Introductionmentioning
confidence: 99%